Medicinal Chemistry of Antisense Oligonucleotides for Therapeutic Use in SARS-CoV-2: Design Strategies and Challenges for Targeted Delivery - Nedaeinia, Reza; Ranjbar, Maryam; Goli, Mohammad; Etebari, Mahmoud; Safabakhsh, Saied; Bayram, Hasan; Ferns, Gordon A.; Tehrani, Helena Moradiyan; Salehi, Rasoul (Current Medicinal Chemistry, 2025)
BackgroundThe evolution of novel Severe Acute Respiratory Syndrome-related Coronavirus 2 (SARS-CoV-2) strains with greater degrees of infectivity, resistance to vaccine-induced acquired immunity, and more severe morbidity have contributed to the recent spread of COVID-19. In light of this, novel therapeutic alternatives with improved effectiveness and fewer side effects have become a necessity. Despite many new or repurposed antiviral agents recommended for Coronavirus disease (COVID-19) therapy, this objective remains unfulfilled. Under these circumstances, the scientific community holds the significant responsibility to develop classes of novel therapeutic modalities to combat SARS-CoV-2 with the least harmful side effects.ObjectiveAntisense Oligonucleotides (ASOs) are short single-stranded oligonucleotides that allow the specific targeting of RNA, leading to its degradation. They may also prevent cellular factors or machinery from binding to the target RNA. It is possible to improve the pharmacokinetics and pharmacodynamics of ASOs by chemical modification or bioconjugation, which may provide conditions for customization of a particular clinical target. This study aimed to outline the potential use of ASOs in the treatment of COVID-19 disease, along with the use of antisense stabilization and transfer methods, as well as future challenges and limitations.MethodsWe have reviewed the structure and properties of ASOs containing nucleobase, sugar, or backbone modifications, and provided an overview of the therapeutic potential, delivery challenges, and strategies of ASOs in the treatment of COVID-19.ResultsThe first-line therapy for COVID-19-infected individuals, as well as the development of oligonucleotide-based drugs, warrants further investigation. Chemical changes in the oligonucleotide structure can affect the biological processes. These chemical alterations may lead to enhanced potency, while changing the pharmacokinetics and pharmacodynamics.ConclusionASOs can be designed to target both coding and non-coding regions of the viral genome to disrupt or completely degrade the genomic RNA and thereby eliminate SARS-CoV-2. They may be very effective in areas, where vaccine distribution is challenging, and they may be helpful for future coronavirus pandemics.
Keywords: ASO delivery